Per-operative conversion of laparoscopic cholecystectomy to open surgery: prospective study at JSS teaching hospital, Karnataka, India - Raza, Mohammed; Venkata, Varaprasad Mandalapu (International Surgery Journal, 2016)
Background:Laparoscopic cholecystectomy has become the standard treatment for symptomatic gall bladder disease. However, there still a substantial proportion of patients in whom Laparoscopic cholecystectomy cannot be successfully performed, and for whom conversion to open surgery is required. Methods: In this study, 800 laparoscopic cholecystectomy performed at JSS teaching hospital from September 2014 to September 2016, were prospectively analyzed. The patients studied included 800, 518 were females (65%) and 282 were males (35%) with a mean age of 44.8 years. From the data collected, only factors available to surgeon preoperatively were considered for analysis. These factors included: age, gender, history of acute cholecystitis, jaundice, previous abdominal surgery, obesity and concomitant disease, ultrasound preoperatively and amp; ERCP. Results:Of the 800 patients who were subjected to laparoscopic cholecystectomy, 23 patients (2.9%) required conversion to open surgery. The most common reason for conversion was dense adhesions, followed by suspicion of CBD injury and inability to define anatomy of calot’s triangle in patients with inflamed, contracted gall bladder (n = 42).Significant predictor factors for conversion were chronic calculous cholecystitis, previous upper abdomen surgeries and CBD injuries . Conclusions:Laparoscopic cholecystectomy has indeed become the gold standard for gall bladder diseases, however a conversion rate of up to 5% is internationally accepted. The conversion rate at our institute was 2.9%. This study shows the pre-operative parameters which enables a surgeon to anticipate need for conversion and hence be prepared.